Integration of Cyber Literature and Reading Skills Critical in Literature Courses in PBSI Project Wisnuwardhana University - Umamy, Etty; Bambang Yulianto; Tengsoe Tjahjono; Syamsul Shodiq (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The progress of science and technology has pushed the writing of literary works into a world without boundaries known as cyber literature. Cyber literature tries to answer the challenges of modernization by becoming a space for imaginative expression. Everyone can express their ideas and imagination on cyber literature. Cyber literature is an interesting medium to study through critical reading activities. At the tertiary level, critical reading skills are raised in the CPL Study Program. In the Indonesian Language and Literature Education Study Program, Wisnuwardhana University, the CPL Study Program is revealed in Literature CPL – MK which can be integrated with cyber literary media and critical reading skills. The Literary MKs are Literary Theory and Aesthetics, Fictional Prose, and Fictional Prose Appreciation. Learning to read critically using cyber literature can be grouped into six structured activities, namely (1) interpreting, (2) analyzing, (3) reasoning, (4) evaluating, (5) explaining, and (6) self-managing. The six activities are a gradual and continuous series.